Kecerdasan emosi dan dukungan atasan terhadap efektivitas kerja karyawan - Widhihastuti, Galih; Ghozali, Ghozali (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2025)
Work effectiveness problems are commonly experienced by organizations and are influenced by psychological and external factors. PT X, as a manufacturing company, has experienced a decline in productivity as indicated by an increase in work errors and delays in task completion, reflecting problems in employee work effectiveness. This study aims to examine the effect of emotional intelligence and supervisor support on employee work effectiveness at PT X. This study employed a quantitative method with an associative design. The research subjects consisted of all 63 employees of PT X in Cikarang, selected using a total sampling technique. The research instrument was a questionnaire, and the data were analyzed using multiple linear regression. The results show that emotional intelligence and supervisor support have a positive and significant effect on employee work effectiveness, both partially and simultaneously. These findings indicate that employee work effectiveness can be improved through effective emotional management and optimal supervisor support. Therefore, companies are encouraged to develop emotional intelligence training programs and strengthen supportive leadership practices to enhance employee work effectiveness